Regulation of Telework in BRICS: Lessons from the Pandemic - M. Chudinovskikh (BRICS Law Journal)
The COVID-19 outbreak forced many employers worldwide to organize remote workplaces and introduce new technologies of labor organization in order to protect employees from the threat of disease. After the pandemic is over, it is reasonable to anticipate an increase in telework. The legal framework of telework continues to evolve unevenly in different countries around the world. The BRICS countries lag behind the United States and the European Union in terms of the legal regulation of telework, and they lack the necessary statistical data collection. The integration of the BRICS countries calls for the development of unified approaches to the legal status of teleworkers. The creation of new jobs in the conditions of the pandemic requires the development of the regulatory framework, analysis of innovative experience and assessment of law enforcement. This article systematizes the approaches of Russian and world scientists to the major issues of telework regulation, including: the conceptual apparatus, the advantages and disadvantages of remote employment, the analysis of legislative initiatives of the BRICS countries in the context of a pandemic and the allocation of best practices, the features of concluding, changing and terminating an employment contract, determining the rights and obligations of teleworkers, the implementation of the right to social partnership, and ensuring labor protection, safety and well-being. The findings of the analysis lead to the conclusion that in order to achieve decent work in digital economy, the BRICS countries need to design a general approach to the regulation of telework for similar to the approach taken by the European Union, and to upgrade existing legislation.